Handy science : Light. ([China] : Educat, 2012)
Discover the wonderful world of light with these 6 exciting experiments which includes 1 x experimental leaflet, 1 x plastic tube, 1 x coloured light filter, 1 x cardboard stencil, 1 x cardboard stand, 1 x periscope, 1 x rubber band, 4 x plastic mirrors, 8 x coloured beads.